Why don’t we consume energy more efficiently? a Lisbon Parish council case study - Barreto, Ana Margarida; Correia de Brito, Nuno; Boechat, Anna Carolina; Oliveira Martins, Luís; Martins, Fernando (Frontiers in Energy Efficiency, 2023)
Almost 50% of European Union's final energy consumption is used for heating and cooling, out of which 80% is used in buildings. The European Commission has recently adopted a clearer priority for the "Efficiency Energy First principle" with a formal recommendation to EU countries to emphasize the importance of prioritizing energy efficiency measures over other energy-related investments. Southern Europe has an old housing stock and has the challenge, as the rest of European Union Member States, to transform it into a decarbonized one.The current exploratory research aims to understand why Portuguese don't consume energy more efficiently and then propose potential interventions. There are several studies that approach the effect of technology-based and behavior-based strategies (individual, socioeconomics and demographics, as well as contextual factors) on energy consumption in a residential context, but few studies that combine all these factors in the same approach, like this research. Based on qualitative research methodology, we analyzed empirical data extracted from a sample of citizens from the same community in Lisbon applying the integrative COM-B model, which considers three core influences of behavior (Capability, Opportunity, and Motivation). We then used the Behavior Change Wheel model to propose interventions that promote energy-responsible behavior in this context.Our findings suggest that there is still a need to invest in structural strategies, and, above all, in behavioral strategies to achieve efficient residential electricity consumption. Specifically, we found that a more efficient energy consumption is mainly limited due to lack of Capability (i.e. people's physical skills and strength, knowledge, and regulation skills). The absence of Motivation (involving habits and self-conscious intentions or beliefs) is the least decisive factor in the adoption of efficient energy consumption behaviors. We therefore recommend the following intervention functions: 1) Training and Enablement to address Physical Capability (associated mainly with the use of high consumption equipment's); 2) Training, Restriction, Environmental restructuring, and Enablement to promote Physical Opportunity (associated with poor home insulation and lack of financial resources to invest in energy solutions); 3) Education, Training, and Enablement to change Psychological Capability (related to the lack of information or confusing information about energy expenditure).